THE ROLE OF COMMUNICATION IN CREATING INCLUSIVE AND COLLABORATIVE LEARNING ENVIRONMENTS - Petrus Jacob Pattiasina; Liyna Karmila Lamaloang; Rengga Yudha Santoso (INJOSEDU: International Journal of Social and Education, 2025)
Communication in the context of inclusive and collaborative education is a dynamic process of interaction between educators and students as well as between students, involving the verbal and non-verbal exchange of information, thoughts and feelings, with the aim of creating a learning environment that supports diversity and promotes cooperation. The research method used in this study is literature research. The results showed that effective communication can create learning spaces that not only support individual needs, but also encourage co-operation and positive interactions between students. It was found that approaches that utilise modern communication technologies such as interactive learning platforms, multimedia tools, and collaborative applications, are able to increase the engagement and participation of all students. However, the research also emphasised the importance of direct interaction and empathy in communication to create a truly responsive and inclusive learning experience.